Helminth infections and hybridization between haemonchus contortus and haemonchus placei in sheep from Santana do Livramento, Brazil - De Almeida, Fabiana Alves [UNESP]; Bassetto, César Cristiano [UNESP]; Amarante, Mônica Regina Vendrame [UNESP]; de Albuquerque, Ana Cláudia Alexandre [UNESP]; Starling, Renan Zappavigna Costa [UNESP]; Do Amarante, Alessandro Francisco Talamini [UNESP] (FapUNIFESP (SciELO), 2018)
The occurrence and intensity of helminth infections were evaluated in sheep from pastures shared with cattle. In 2015 and 2016, young male sheep acquired in Santana do Livramento, Rio Grande do Sul, Brazil, were finished in integrated crop-livestock system. We selected the 12 sheep that showed the highest number of nematode eggs per gram of faeces to search for worms in the gastrointestinal tract. Haemonchus contortus and Trichostrongylus colubriformis were the major parasites. H. contortus presented mean intensities of 1,159 and 257 worms in 2015 and 2016, respectively. T. colubriformis displayed mean intensities of 4,149 and 2,427 worms in 2015 and 2016, respectively. Of the 127 male specimens of Haemonchus spp. analysed by Polymerase Chain Reaction (PCR), 125 were H. contortus, one Haemonchus placei and one hybrid. Other species detected were Cooperia punctata, Cooperia pectinata, Cooperia spatulata, Cooperia curticei, Ostertagia ostertagi, Teladorsagia circumcincta, Trichostrongylus axei, Nematodirus spathiger, and Trichuris ovis. Twenty lambs presented cysts of Taenia hydatigena in the liver and mesentery. One lamb presented Coenurus cerebralis, the larval stage of Taenia multiceps, in the brain. In conclusion, sheep from pasture shared with cattle presented a high diversity of nematode species. H. contortus and H. placei co-infection occur with consequent hybridization.
Infecções helmínticas e hibridização entre haemonchus contortus e haemonchus placei em ovinos criados em Santana do Livramento, Brasil
Keywords: Cooperia; Nematodirus; Ostertagia; Taenia hydatigena; Teladorsagia; Trichostrongylus